Expulzarea în dreptul contravențional – atentare asupra drepturilor și libertăților fundamentale ale omului sau o protejare a acestora? - Crainic, Adrian (Print-Caro, 2023)
This communication reveals the nature and character of the expulsion in the Contravention Law, which is related to the efficient analysis of these security measures in the sense of respecting the Fundamental Human Rights and Freedoms. In the content of the paper will be reviewed: the general peculiarity of the legal institution of expulsion to be present in general in the normative-legal field, referring specifically to which branches of persistent law; the analysis of the expulsion in the Contravention Law by virtue of the contravention legal norms; evidence of the frequency of this security measure applicable in the territory of our country; proposals for lex ferenda; appreciation of the legal effect of these institutions in relation to the nature of fundamental human rights and freedoms.

Prin prezenta comunicare este relevată natura și caracterul expulzării în Dreptul Contravențional, care este raportată la analiza eficacității acestei măsuri de siguranță în sensul respectării Drepturilor și Libertăților Fundamentale ale Omului. În cuprinsul lucrării va fi trecut în revistă : particularitatea generală a instituției juridice a expulzării de a fi prezentă la general în sistemul normativjuridic, făcându-se referință anume în care ramuri de drept persistă; analiza expulzării în Dreptul Contravențional în virtutea normelor juridice contravențional; evidența fregvenței acestei măsuri de siguranță aplicabile pe teritoriul țării noastre; propuneri de lege ferenda; aprecierea efectului juridic al acestei instituții în raport cu natura drepturilor și libertăților fundamentale ale omului.
Keywords: expulsion; contravention; security measures; foreign citizen; stateless person; expulzare; contravenție; măsuri de siguranță; cețățean străin; apatrid; contravenient